PEMBELAJARAN BERBASIS PENDEKATAN STEAM MELALUI PROJECT-BASED LEARNING (PJBL) UNTUK MENINGKATKAN LITERASI SAINS SISWA SEKOLAH DASAR - Ramadhan, Wandri (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2023)
This research is motivated by the urgency of scientific literacy for elementary school students in the context of science learning in fourth-grade classes. The objective of this study is to evaluate the effectiveness of implementing the STEAM (Science, Technology, Engineering, Arts, Mathematics) approach through Project-Based Learning (PjBL) methods in enhancing the scientific literacy of elementary school students. The selection of this research topic is based on the pressing need to strengthen scientific literacy as an essential skill in facing the advancements in science and technology in the modern era. The research method employed in this study is a quasi-experimental design with both a control group and a treatment group. The research sample consists of randomly selected fourth-grade students from elementary schools. The control group receives conventional learning, while the treatment group undergoes STEAM-based learning through PjBL. The results of the study indicate that the implementation of the STEAM approach through PjBL has a significant positive impact on the improvement of students' scientific literacy. Students engaged in STEAM-based learning show enhanced understanding of scientific concepts, observational skills, critical thinking abilities, and superior communication skills compared to their counterparts undergoing conventional learning. In conclusion, the implementation of the STEAM approach through PjBL holds substantial potential for enhancing scientific literacy among elementary school students.